Implementasi Konvensi International Basel Terhadap Impor Sampah di Tiongkok - Gina Sonia Te'dang (Journal of International and Local Studies, 2020)
As a member of the Basel convention, China is committed to strictly limiting the import of plastic waste in order to maintain the quality of the country's environment. This study aims to determine and analyze the implementation of the Basel International Convention on handling waste imports in China. The research method used was a qualitative method with a descriptive approach. Data collection was carried out through literature review. The results show that the implementation of the Basel International Convention in handling waste imports in China has been successful, in terms of indicators of successful policy implementation, namely; content of policy and context of implementation. The implementation results show that China's policy of closing waste imports through the Green Fence Operation Policy and the National Sword Policy has a positive impact on reducing the amount of waste imports entering China. This decline has also affected changes in China's environment, be it water quality, air and those polluted by garbage. Although the changes still require a lot of improvement efforts, the success of implementation is also influenced by the Xi Jinping government regime which supports environmental reforms towards development progress with attention to ecological protection.